2017
DOI: 10.1111/1346-8138.13866
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of factors influencing successful skin grafting for patients with skin cancer of the foot

Abstract: Skin grafting is a simple method for reconstruction of a large defect on the foot. Although skin grafting on the foot sometimes fails, it is not clear what factors influence the success rate of skin grafting. We analyzed data for 71 patients with skin cancer of the foot who underwent reconstruction of defects with skin grafting. The factors we evaluated were success rate of skin grafting, weight-bearing or non-weight-bearing area, immediate or delayed reconstruction, and whether a tie-over bolster was used or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Local reconstruction techniques include the use of grafts and flaps [5]. Successful grafting requires adequate blood flow to the recipient site, immobilization of the skin graft, and prevention of fluid collection formation under the graft [30].…”
Section: Discussionmentioning
confidence: 99%
“…Local reconstruction techniques include the use of grafts and flaps [5]. Successful grafting requires adequate blood flow to the recipient site, immobilization of the skin graft, and prevention of fluid collection formation under the graft [30].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence Quality: Low Recommendation Strength: Option Recommendation 1: Rationale (Table 3) Reconstruction can be performed immediately following excision of a skin cancer, or reconstruction can be delayed until days, weeks, or even months later. [6][7][8][9][10][11][12][13][14] At least three studies of low to moderate quality have compared immediate to delayed reconstruction for relative functional and aesthetic outcomes. [6][7][8] A low-quality study found that a 1-month interval before reconstruction improved survival of grafts of the foot, 6 but a moderate-quality study of grafts at various anatomic locations detected no reduction in partial graft necrosis when reconstruction was delayed 1 to 8 days.…”
Section: Recommendationsmentioning
confidence: 99%
“…Optimal stabilization of the graft is essential to prevent skin graft loss. The tie-over technique is one of the most common methods for the stabilization of skin graft in Japan; 1 however, cases with significant graft loss due to insufficient graft stabilization sometimes occur, especially with large and/or muscleexposed skin defects.…”
Section: Introductionmentioning
confidence: 99%